Don't Look at Me : A Child's Book About Feeling Different - Sanford, Doris; Evans, Graci (Portland, Or. : Multnomah Press, 1986)
Patrick couldn't read, spell, or do math problems as well as the other children in his class and they teased him. They called him dumb until he believed he was dumb, but someone helped him feel better about himself.
Cover title.
Keywords: Self-esteem -- Fiction; Mentally handicapped -- Fiction; Self-respect -- Fiction; Self-acceptance